Investigation of Performance and Emissions Characteristic of Single Cylinder CI Engine Using High Blend Biodiesel - Mohamad Azmeer Iskandar Nordin; Md Norrizam Mohmad Ja’at; Shaiful Fadzil Zainal Abidin (Progress in Engineering Application and Technology, 2025)
This research examines the performance and emissions characteristics of a single-cylinder CI engine using high-blend biodiesel fuels (B10, B20, B30, and B40) under controlled conditions. Measurements included engine power, torque, brake specific fuel consumption (BSFC), thermal efficiency, and emissions of NOx, CO, HC, and C02. The results indicated that B20 offered the best balance of power output and fuel economy, while higher blends (B30 and B40) significantly reduced CO and HC emissions but increased NOx emissions due to their higher oxygen content. The study revealed trade-offs between efficiency and environmental impact, as the viscosity and oxygen content of biodiesel blends affected key parameters like BSFC and emissions. Despite these trade-offs, biodiesel blends demonstrated stable combustion and adaptability across different loads and speeds. The findings highlight the potential of biodiesel as a sustainable energy source, underscoring the importance of NOx mitigation strategies to enhance its viability as a cleaner alternative to fossil fuels.